2016
DOI: 10.3390/ijerph13111080
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns in Relation to General and Central Obesity among Adults in Southwest China

Abstract: Dietary patterns represent a broader picture of food consumption, and are better correlated with a variety of health outcomes. However, few studies have been conducted to explore the associations between dietary patterns and obesity in Southwest China. Data from the 2010–2012 National Nutrition Survey in the province of Yunnan, Southwest China, were analyzed (n = 1604, aged 18–80 years). Dietary data were collected using the 24 h dietary recall over three consecutive days. Height, weight, and waist circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 38 publications
3
27
2
2
Order By: Relevance
“… 3 Coarse cereals and tubers can provide rich dietary fibre, less fat and less protein than animal food. 12 Similar to a study of middle-aged and elderly Japanese people, 6 we found that dietary fibre intake had a marginally significant difference among altered MetS components groups 0, 1, 2 and 3–5 overall. Other data indicated that the protective role of fibre from cereals was higher than that of fibre from other sources against the development of MetS and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“… 3 Coarse cereals and tubers can provide rich dietary fibre, less fat and less protein than animal food. 12 Similar to a study of middle-aged and elderly Japanese people, 6 we found that dietary fibre intake had a marginally significant difference among altered MetS components groups 0, 1, 2 and 3–5 overall. Other data indicated that the protective role of fibre from cereals was higher than that of fibre from other sources against the development of MetS and type 2 diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…According to the definition of WHO, adults who smoked at least one cigarette a day are defined as current smokers. 12 To determine alcohol consumption, individuals were asked the question: 'Have you consumed alcohol (beer, wine or other alcoholic beverage) during the past year (yes, no)?'. 2 Residence was divided into urban and rural, and geographical region was divided into the North (Liaoning, Heilongjiang, Henan and Shandong) and the South (Hunan, Hubei, Jiangsu, Guangxi and Guizhou).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the meat pattern which was defined as high intake of chickens, beef, lamb, duck, goose in a previous study [ 36 ], the ‘Tuber and meat’ pattern in the present study was loaded heavily on tuber. The tuber rich in dietary fiber was reported to be inversely associated with obesity and positively associated with underweight [ 37 ]. The dietary fiber has the antihypertensive effects as well as the prevention of a number of cardiovascular diseases [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%